Inflammatory myofibroblastic tumors: Diagnostic challenges and treatment strategies - A case report and literature review - Betul Kinik; Seda Tural Onur; Asli Bicen; Kaan Kara; Cemal Aker (Respiratory Medicine Case Reports)
Inflammatory myofibroblastic tumors (IMTs) are rare benign mesenchymal tumors that present diagnostic challenges due to their diverse clinical and radiological manifestations. We present a case of a 19-year-old female with a history of intermittent hemoptysis. Imaging studies suggested a mediobasal lung lesion, prompting further evaluation. Bronchoscopy revealed vascular changes, and PET imaging indicated high metabolic activity. A left lower lobectomy was performed for diagnostic and therapeutic purposes, confirming the diagnosis of IMT characterized by spindle cell proliferation and inflammatory infiltrates. Surgical resection remains the cornerstone treatment, offering favorable outcomes with rare recurrence. Follow-up underscores the importance of monitoring and assessing prognostic factors to optimize patient management.